Meaningful Learning of Physics for Student Athletes at Sports Schools - Longa Martínez, Tomasa Magaly (Rastros Rostros, 2015)
Introduction: the purpose of this article is to explain the importance of achieving meaningful learning of physics in student athletes. The distinctive features of developmental teaching are discussed, emphasizing meaningful learning as one of its pillars. Methodology: this research employed different theoretical and empirical methods. Among the former, the historical-logical method, analysis and synthesis, and document analysis were used. The systemic-structural method was used to develop a system of methodological recommendations. Results: finally, the results are shown and the implementation of the strategy is highlighted in order to ensure that the contents of physics are meaningful to student athletes and thus improve their academic performance. Conclusions: it is essential that the contents and laws of physics are related to specific sports situations and, thus, it is demonstrated how the correct application to these regularities contributes to athletic success
Keywords: meaningful learning; athletes; physics; teaching-learning process